Baśń dramatyczna − zapomniane ogniwo - Nabiałek, Magda (Zagadnienia Rodzajów Literackich, 2019)
A dramatic fairy tale is the expression of a specific historical moment. At the turn of the 19th and 20th century original forms of dialogue with tradition and new ways of developing literature were searched at the same time. It seems that the dramatic tale — absent in most compendiums devoted to the literature of modernism — is one of the best examples of unstable forms that reflect in their structure the dilemmas accompanying the writing at the turn of the 19th and 20th century. What matters here is a specific type of folklore and links with the fairy-tale play and commedia dell’ arte.